Feminitives with Suffix ‘-shits(a ) /-chits(a)’ - Zoya I. Mineeva (Научный диалог)
The feminitives (nouns denoting women) of the modern Russian language, formed with the help of the productive suffixal morpheme ‘-shits(a) /-chits(a)’ are considered. The views of scientists of the 19th-21st centuries on the process of derivation of feminine nouns are characterized. The relevance of the study is due to the stable productivity of the suffix formant and the insufficient development of the theory of word formation of feminitives. Structural-semantic and corpuscular methods are used. The novelty and scientific significance of the work is determined primarily by the research material: neologisms, which are included in the dictionaries of new words of 1971-2014, the Russian National Corpus (main and newspaper corps) used in media texts, are analyzed. The specifics of correlates of male and female gender fixing in the explanatory dictionaries of the last years of publication are shown. Particular attention is paid to the semantics of neoplasms, a classification of new feminitives by semantic properties is proposed. Motivating words, morphological features of the compound of the formant with the motivating basis are revealed. The author dwells on potential neologisms. The conclusion is made that the formation of feminitives with suffixes ‘-shits(a ) /-chits(a)’, as well as masculine nouns with value of a person, is carried out using verbs and deverbatives, nouns and adjectives.